DISTRIBUSI ZAKAT DAN PEMBERDAYAAN EKONOMI UMAT - Mubasirun Mubasirun (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
Zakat in Central Java is estimated to reach Rp 9,356 trillion each year, derivedfrom zakat, infak and sedekah (ZIS) Rp 8,982 trillion and Rp 374.275 billionzakat fitrah. This is derived from the assumption that most Moslem give ZIS Rp.1 million each year. The purpose of this research is informing the meaning of zakat as recited in Surah Attaubah verse 60, how the zakat was distributed and observing the effectiveness of zakat in the relation with economic empowerment. Techniques in analyzing the data were domain, taxonomy, components and theme analysis. The finding showed that zakat distribution was dominated by consumption distribution. On the other hands productive distribution was not regards. But it is interesting to be noticed that distribution of zakat funds committed by the institutions of zakat distribution pattern dominated by the cost living in various pattern of their varieties While distribution patterns that rely on productive among the educated (scholars) are ignored by board of charity